Prospect theory and tax evasion: A reconsideration of the Yitzhaki Puzzle - Amedeo Piolatto; Matthew Rablen (Institute for Fiscal Studies (IFS), 2013)
The standard expected utility model of tax evasion predicts that evasion is decreasing in the marginal tax rate (the Yitzhaki Puzzle). The existing literature disagrees on whether prospect theory overturns the puzzle. We disentangle four distinct elements of prospect theory and find loss aversion and probability weighting to be redundant in endogenous specification of the reference level. These classes include, as special cases, the most common specifications in the literature. New specifications of the reference level are needed, we conclude.
Keywords: H26; D81; K42; 330; prospect theory; tax evasion; Yitzhaki puzzle; stigma; diminishing sensitivity; reference dependence; endogenous audit probability; endogenous reference level